Effects of fiscal regime changes on investment climate of Malaysia’s marginal oil fields: Proposed model - Abdul Manaf, Nor Aziah; Saad, Natrah; Ishak, Zuaini; Mas’ud, Abdulsalam (Elsevier Ltd, 2014)
The paper proposes a model to examine the effect of the 2010 fiscal regime changes on investment climate of Malaysia’s marginal oil fields.It proposes the use of investment appraisal tools, such as Net Present Value, Internal Rate of Return, Profitability Index, Saving Index and Access to Gross Revenue, for the study.Two scenarios would be considered using the fiscal terms of Production Sharing Contract (PSC) and Risk Service Contract (RSC), respectively.Each scenario would be of a fifteen-year simulation. Sensitivity analysis will also be conducted for both the scenarios under different prices and reserves levels.The study, when undertaken, will be beneficial to both industry and the government.